Evaluation of headache in children: a retrospective study - Ekici, Arzu; Yimenicioglu, Sevgi; Carman, Kursat; Kocak, Ozan; Yarar, Coskun; Yakut, Ayten (The European Research Journal, 2015)
Objectives. Headache is a very common symptom that can be seen in the children. It can be seen due to primary or secondary causes. Migraine and tension-type headache are the most commonly seen primary headache types in children. In this study, we retrospectively evaluate etiologic and clinical features of the 228 patients. Methods. In this study, clinical features and neuro-imaging characteristics of the patients, who admitted Eskisehir Osmangazi University pediatric neurology department between 2007 and 2011 were evaluated retrospectively. Headache classification was made according to "International Headache Society" criteria. Results. The ages of the patients ranged from 4 to 18 years (average 12.9±3.1). There were 136 (59.6 %) girls, and 92 (40.4%) boys. The most frequent causes of the headache were migraine (37.3%) and tension type headache (25%). There were other associating diseases at 54 (23.7%) patients. Allergic rhinitis and asthma bronchilitis were the most commonly associated diseases. Abnormalities were encountered in 3 (6.8%) of the 44 (19.3%) patients taken computerized brain tomography, 18 (20.2%) of the 89 (39%) patients taken magnetic resonance imaging and 8 (3.5%) of the 77 (33.8%) patients taken electroencepahlography. No serious problem is established in patients undergoing neuro-imaging. Conclusions. In this study, it was seen that migraine and tension-type headache are the most frequently seen causes of the headache in the children. It is concluded that unnecessary neuroimaging examination should be avoided by detailed anamnesis and neurologic examination of children that admitted hospital with headache complaint.